Soluble HLA‐G is a differential prognostic marker in sequential colorectal cancer disease stages. Issue 11 (24th March 2017) - Kirana, Chandra; Ruszkiewicz, Andrew; Stubbs, Richard S.; Hardingham, Jennifer E.; Hewett, Peter J.; Maddern, Guy J.; Hauben, Ehud
Abstract : The expression of HLA‐G by tumour cells is an established mechanism to escape recognition and immune mediated destruction, allowing tumour survival, growth and metastasis. However, the prognostic value of soluble HLA‐G (sHLA‐G) remains unknown. Mucinous carcinoma (MC) is a distinct form of colorectal cancer (CRC) found in 10 to 15% of patients, which has long been associated with poor response to treatment. To investigate the prognostic value of plasma sHLA‐G levels in CRC patients, preoperative plasma sHLA‐G levels were determined by ELISA in CRC patients ( n = 133). In addition, the local expression of HLA‐G in tumour biopsies was assessed using tissue microarray analysis ( n = 255). Within the high 33rd percentile of sHLA‐G levels (265–890 U/mL; n = 44) we observed higher frequency of MC patients ( p = 0.012; Chi‐square), and higher sHLA‐G levels in patients with vascular invasion ( p = 0.035; two‐tailed t ‐test). Moreover, MC patients had significantly higher sHLA‐G levels compared to those with adenocarcinoma not otherwise specified ( p = 0.036; two‐tailed t ‐test). Surprisingly, while stage II patients showed negative correlation between sHLA‐G levels and liver metastasis free survival (LMFS) ( p = 0.041; R = −0.321), in stage III patients high sHLA‐G levels were associated with significantly longer LMFS ( p = 0.002), and sHLA‐G levels displayed positive correlation with LMFS ( p = 0.006; R = 0.409). High HLA‐G expression in tumours was associated with poor cancer specific overall survival in stage II to III ( p = 0.01), and with shorter LMFS in stage II patients ( p = 0.004). Our findings reveal that sHLA‐G levels are associated with distinct progression patterns in consecutive disease stages, indicating a potential value as surrogate marker in the differential prognosis of CRC. Abstract : What's new? The majority of colorectal cancer (CRC)‐related deaths are attributable to liver metastasis. However, there is no prognostic biomarker that predicts metastatic risk and allows informed selection of preventive treatment. The translational challenge, therefore, is to develop surrogate markers of metastatic progression. HLA‐G expression by tumours is an established immune escape mechanism, and so the present study set to determine the prognostic value of circulating soluble HLA‐G in different CRC stages. The findings reveal that sHLAG levels are associated with distinct progression patterns in consecutive disease stages, indicating its potential value as a surrogate marker in the differential prognosis of CRC.